High Incidence of Noonan Syndrome Features Including Short Stature and Pulmonic Stenosis in Patients carrying NF1 Missense Mutations Affecting p.Arg1809: Genotype–Phenotype Correlation. Issue 11 (21st August 2015) - Rojnueangnit, Kitiwan; Xie, Jing; Gomes, Alicia; Sharp, Angela; Callens, Tom; Chen, Yunjia; Liu, Ying; Cochran, Meagan; Abbott, Mary‐Alice; Atkin, Joan; Babovic‐Vuksanovic, Dusica; Barnett, Christopher P.; et al.
ABSTRACT Neurofibromatosis type 1 (NF1) is one of the most frequent genetic disorders, affecting 1:3, 000 worldwide. Identification of genotype–phenotype correlations is challenging because of the wide range clinical variability, the progressive nature of the disorder, and extreme diversity of the mutational spectrum. We report 136 individuals with a distinct phenotype carrying one of five different NF1 missense mutations affecting p.Arg1809. Patients presented with multiple café‐au‐lait macules (CALM) with or without freckling and Lisch nodules, but no externally visible plexiform neurofibromas or clear cutaneous neurofibromas were found. About 25% of the individuals had Noonan‐like features. Pulmonic stenosis and short stature were significantly more prevalent compared with classic cohorts (P < 0.0001). Developmental delays and/or learning disabilities were reported in over 50% of patients. Melanocytes cultured from a CALM in a segmental NF1‐patient showed two different somatic NF1 mutations, p.Arg1809Cys and a multi‐exon deletion, providing genetic evidence that p.Arg1809Cys is a loss‐of‐function mutation in the melanocytes and causes a pigmentary phenotype. Constitutional missense mutations at p.Arg1809 affect 1.23% of unrelated NF1 probands in the UAB cohort, therefore this specific NF1 genotype–phenotype correlation will affect counseling and management of a significant number of patients.